The fission yeast SPB component Dms1 is required to initiate forespore membrane formation and maintain meiotic SPB components - Niimi, Touko (PLoS One, 2018)
The spindle pole body (SPB) plays a central role in spore plasma membrane formation in addition to its recognized role in microtubule organization. During meiosis, a biomembrane called the forespore membrane (FSM) is newly formed at the SPB. Although several SPB proteins essential for the initiation of FSM formation (meiotic SPB components) have been identified, the molecular mechanism is still unknown. Here, we report the isolation and functional characterization of Dms1 as a component of the SPB. We show that FSM formation does not initiate in dms1Δ cells. Dms1 protein is constitutively expressed throughout the life cycle and localizes to the SPB and the nuclear envelope. The predicted Dms1 protein has a transmembrane domain, which is required for correct localization at the SPB. Dms1 is essential for the proper localization of three meiotic SPB components, Spo15, Spo2, and Spo13, but these components do not affect localization of Dms1. Collectively, these results suggest that Dms1 anchors these meiotic SPB components to the SPB, thereby facilitating the initiation of FSM formation.